Penggunaan Media Video Pembelajaran untuk Meningkatkan Motivasi dan Hasil Belajar Pelajaran PKN Kelas IV B SDI Harekakae - Friska Luruk; Marsela Luruk Bere; Yanuarius Bria Seran; Yuventius Tamelab; Damian Puling (Jurnal Pendidikan Dirgantara, 2025)
In choosing learning video media according to learning objectives and student characteristics and optimizing the Use of Learning Video Media that can improve student motivation and learning outcomes, it is necessary to have learning video media so that learning objectives can be achieved. The use of video media in this learning process aims to determine how the Use of learning video media to improve motivation and learning outcomes of Civics lessons in Class IV B SDI Harekakae. This study was conducted in two learning cycles with 22 students as research subjects, where the learning test results achieved by students who achieved KKM completion were only 14 students with a score of 63.64%, the remaining 8 students or 36.36% who had not achieved KKM completion in cycle I who had not achieved the expected learning objectives due to lack of student participation in the learning process. So that making improvements in cycle II, a very significant increase was seen where from the learning results of cycle I only 63.64% of students completed, then in cycle II students who completed according to the completion criteria (KKM) were 21 people, the remaining 1 person with a score of 95.45%. This shows that students in cycle II have met the KKM standards in learning.